Rectal budesonide and mesalamine formulations in active ulcerative proctosigmoiditis: efficacy, tolerance, and treatment approach - Christophi, George P (Clin Exp Gastroenterol, 2016)
Ulcerative colitis (UC) is an immune-mediated disease of the colon that is characterized by diffuse and continuous inflammation contiguous from the rectum. Half of UC patients have inflammation limited to the distal colon (proctitis or proctosigmoiditis) that primarily causes symptoms of bloody diarrhea and urgency. Mild-to-moderate distal UC can be effectively treated with topical formulations (rectal suppositories, enemas, or foam) of mesalamine or steroids to reduce mucosal inflammation and alleviate symptoms. Enemas or foam formulations adequately reach up to the splenic flexure, have a minimal side-effect profile, and induce remission alone or in combination with systemic immunosuppressive therapy. Herein, we compare the efficacy, cost, patient tolerance, and side-effect profiles of steroid and mesalamine rectal formulations in distal UC. Patients with distal mild-to-moderate UC have a remission rate of approximately 75% (NNT =2) after treatment for 6 weeks with mesalamine enemas. Rectal budesonide foam induces remission in 41.2% of patients with mild-to-moderate active distal UC compared to 24% of patient treated with placebo (NNT =5). However, rectal budesonide has better patient tolerance profile compared to enema formulations. Despite its favorable efficacy, safety, and cost profiles, patients and physicians significantly underuse topical treatments for treating distal colitis. This necessitates improved patient education and physician familiarity regarding the indications, effectiveness, and potential financial and tolerability barriers in using rectal formulations.